2015
DOI: 10.1017/dmp.2015.24
|View full text |Cite
|
Sign up to set email alerts
|

Core Competencies in Disaster Management and Humanitarian Assistance: A Systematic Review

Abstract: Disaster response demands a large workforce covering diverse professional sectors. Throughout this article, we illustrate the results of a systematic review of peer-reviewed studies to identify existing competency sets for disaster management and humanitarian assistance that would serve as guidance for the development of a common disaster curriculum. A systematic review of English-language articles was performed on PubMed, Google Scholar, Scopus, ERIC, and Cochrane Library. Studies were included if reporting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 42 publications
(140 reference statements)
1
30
0
2
Order By: Relevance
“…It comprised four items: (a) Korea is geopolitically vulnerable to disasters; (b) A disaster can paralyze social functions such as shutting down transportation, communication, and power networks, threatening public safety and national security, and so on; (c) A disaster can cause economic crises such as inflation, pricing bubbles, and so on; (d) I think that the area I live in has a high likelihood of future disaster occurrence since a detailed safety inspection of the buildings is not conducted regularly. Each item is measured using a 5-point Likert scale, ranging from "strongly disagree (1)" to "strongly agree (5)." The range of possible total scores is from 4 to 20.…”
Section: Disaster Risk Perceptionmentioning
confidence: 99%
See 3 more Smart Citations
“…It comprised four items: (a) Korea is geopolitically vulnerable to disasters; (b) A disaster can paralyze social functions such as shutting down transportation, communication, and power networks, threatening public safety and national security, and so on; (c) A disaster can cause economic crises such as inflation, pricing bubbles, and so on; (d) I think that the area I live in has a high likelihood of future disaster occurrence since a detailed safety inspection of the buildings is not conducted regularly. Each item is measured using a 5-point Likert scale, ranging from "strongly disagree (1)" to "strongly agree (5)." The range of possible total scores is from 4 to 20.…”
Section: Disaster Risk Perceptionmentioning
confidence: 99%
“…At all disaster levels, disaster response competency refers to the specialized knowledge and skills associated with disasters as the capacity required for EMTs [4,5]. The questionnaire was a modified version of the one used by Uhm et al [19] and was based on the onscene emergency care guidelines for EMTs in South Korea [20] and expert group consultations.…”
Section: Disaster Response Competencymentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these medical surveys are showed that children are more vulnerable than an adult person when disaster strikes [26]. In respect to clinical and field research in paediatrics, some research provides that people have to more care about their children in any catastrophic situation [29,30].People in disaster are waiting for help in order to recover them by emergency relief services, public services or local volunteers [31][32][33][34][35][36][37]. Search and rescue teams are working hard in the disaster area.…”
mentioning
confidence: 99%